Challenges Faced by English Teachers 21st Century at Vocational School in East Kalimantan - Naiyah*, Iis; Rachman, Dzul (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This study examines the challenges faced by English teachers at vocational schools in East Kalimantan, Indonesia, amid the demands of the 21st century. It higlights the significant obtacles teachers encounter, including inadequate resources and facilities, which affect the quality of education. Using qualitative methods such as interviews, observations, and document analysis, the research provides an in-depth understanding of these challenges. The findings reveal that english teachers struggle with limited access to update learning materials and technology-based teaching tools. Purposive sampling was used to select experienced informants, ensuring the collecting of accurate and rich data. The study aims to offer insight and recommendations to improve the quality of English education in vocational schools, addressing resources limitations and fostering better learning outcomes for students in East Kalimantan.